2010
DOI: 10.1073/pnas.0914380107
|View full text |Cite
|
Sign up to set email alerts
|

Repeated loss of coloniality and symbiosis in scleractinian corals

Abstract: The combination of coloniality and symbiosis in Scleractinia is thought to confer competitive advantage over other benthic invertebrates, and it is likely the key factor for the dominance of corals in tropical reefs. However, the extant Scleractinia are evenly split between zooxanthellate and azooxanthellate species. Most azooxanthellate species are solitary and nearly absent from reefs, but have much wider geographic and bathymetric distributions than reef corals. Molecular phylogenetic analyses have repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 51 publications
6
106
0
1
Order By: Relevance
“…Therefore, these genes are more informative for reconstructing deep coral phylogenies. Other than the 16S rDNA that established widespread subordinal non-monophyly Palumbi 1996, 1997;Le GoffVitry et al 2004), 12S rDNA, cytochrome b and cytochrome c oxidase subunit I (COI) were purposed for corals relatively early (Medina et al 1999;van Oppen et al 1999;Fukami et al 2000) and have been used for inferring large scleractinian trees effectively (Chen et al 2002;Fukami et al 2004bFukami et al , 2008Barbeitos et al 2010;Kitahara et al 2010bKitahara et al , 2013Stolarski et al 2011;Arrigoni et al 2012Arrigoni et al , 2014cHuang 2012;Huang andRoy 2013, 2015;Marcelino et al 2013;Curnick et al 2015; Fig. 4.1).…”
Section: The Rise Of Molecular Phylogenetic Methodsmentioning
confidence: 99%
“…Therefore, these genes are more informative for reconstructing deep coral phylogenies. Other than the 16S rDNA that established widespread subordinal non-monophyly Palumbi 1996, 1997;Le GoffVitry et al 2004), 12S rDNA, cytochrome b and cytochrome c oxidase subunit I (COI) were purposed for corals relatively early (Medina et al 1999;van Oppen et al 1999;Fukami et al 2000) and have been used for inferring large scleractinian trees effectively (Chen et al 2002;Fukami et al 2004bFukami et al , 2008Barbeitos et al 2010;Kitahara et al 2010bKitahara et al , 2013Stolarski et al 2011;Arrigoni et al 2012Arrigoni et al , 2014cHuang 2012;Huang andRoy 2013, 2015;Marcelino et al 2013;Curnick et al 2015; Fig. 4.1).…”
Section: The Rise Of Molecular Phylogenetic Methodsmentioning
confidence: 99%
“…The taxonomic relevance of the solitary condition in corals has been revised in light of molecular phylogeny reconstructions published in recent years. Barbeitos, Romano, and Lasker (2010) provided robust phylogenetic evidence that polystomatism has been repeatedly acquired and/or lost throughout the history of the order Scleractinia. These findings have been subsequently corroborated by detailed phylogenetic analyses revealing that evolution from a solitary to a colonial condition, and the reverse, in the Fungiidae and Dendrophylliidae Gray, 1847, has occurred frequently in these two families characterized by congeneric monostomatous and polystomatous species (Arrigoni et al, 2014c;Gittenberger et al, 2011).…”
Section: The Relevance Of Being Solitarymentioning
confidence: 97%
“…This appears to have merit. Severance of the link between corals and photosymbionts was proposed to explain the reef collapse at the end of the Late Triassic (Stanley and Van de Schootbrugge, 2009) and recent molecular analysis has revealed that both coloniality and symbiosis were repeatedly acquired and or lost throughout the history of the Scleractinia (Barbeitos et al, 2010).…”
Section: Introductionmentioning
confidence: 98%